RESPONS PETERNAK SAPI PERAH TERHADAP PEMBUATAN YOGHURT SUSU SAPI DENGAN PENAMBAHAN PUREE UBI JALAR (Ipomea batatas) DI DESA GEDAWANG KECAMATAN BANYUMANIK KOTA SEMARANG (The Response of Dairy Cow Farmer’s to Cow’s Milk Yoghurt Production With The Additional Sweet Potatoes Puree (Ipomea batatas) In Gedawang Village Banyumanik District Semarang City) - ROSALIA ROSALIA; MUHAMAD RUSLIYADI; SUNARSIH SUNARSIH (Universitas Mulawarman (University of Mulawarman), 2022)
The objectives of the research were to find out: 1) the response of dairy cow farmers to cow's milk yogurt production with the addition of sweet potato puree; 2) the factors (age, education level, experience of breeding and intensity of extension) that affect the response of dairy cow farmers; 3) the effectiveness of extension and the effectiveness of behavior shift of dairy cow farmers. This research used one group pretest-posttest design and the sampling technique used was the saturated sample technique (census) so that 30 respondents were obtained. The results of data analysis showed that the response of dairy cow farmers inGedawang Village, Banyumanik District was in the